Fermented and Germinated Processing Improved the Protective Effects of Foxtail Millet Whole Grain Against Dextran Sulfate Sodium-Induced Acute Ulcerative Colitis and Gut Microbiota Dysbiosis in C57BL/6 Mice - Zhang, Yuhan; Liu, Wei; Zhang, Di; Yang, Yanbing; Wang, Xianshu; Li, Lingfei (Frontiers in Nutrition, 2021)
This study investigated the effects of foxtail millet whole grain flours obtained through different processing methods on alleviating symptoms and gut microbiota dysbiosis in a dextran sulfate sodium (DSS)-induced murine colitis model. Sixty C57BL/6 mice were divided into six groups (n = 10 in each group), including one control group (CTRL) without DSS treatment and five DSS-treated groups receiving one of the following diets: AIN-93M standard diet (93MD), whole grain foxtail millet flour (FM), fermented (F-FM), germinated (G-FM), and fermented-germinated foxtail millet flour (FG-FM). A comparison of the disease activity index (DAI) demonstrated that foxtail millet whole grain-based diets could alleviate the symptoms of enteritis to varying degrees. In addition, 16S rRNA gene sequencing revealed that FG-FM almost completely alleviated DSS-induced dysbiosis. Mice on the FG-FM diet also had the lowest plasma IL-6 levels and claudin2 expression levels in the colon, indicating reduced systemic inflammation and improved gut barrier function. This study suggested that foxtail millet whole grain is an attractive choice for the intervention of IBD and gut microbiota dysbiosis, and its prebiotic properties are highly affected by the processing methods.